Immigrant Social and Cultural Life in Literature - Chapkina, Nadejda; Jaret, Charles; Liu, Guangya; Pollock, Angela (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Novels and short stories about the immigrants’ experiences, either in their homeland or their new country, are popular literary forms. These offer insiders’ perspectives on what life is like for an immigrant or second generation Americans. The following list contains some excellent recent stories and some classic old ones.